Distributed smart antenna system for high‐density WLAN system. Issue 6 (1st March 2018) - Ishihara, K.; Murakami, T.; Abeysekera, H.; Akimoto, M.; Takatori, Y.
Abstract : The authors propose a WLAN with a distributed smart antenna system (D‐SAS) that can suppress interference and improve the system throughput in high‐density scenarios such as stadiums and shopping malls. The authors also demonstrate a prototype of the WLAN with D‐SAS and show experimental results in which the proposed system achieves more than twice the throughput of a conventional WLAN system with a centralised antenna system.